Enhancing flange length in stamping of high strength steel sheets sm520b using stretch flanging method - Mohd Syafiq, Yusoff (2020)
Nowadays, high strength steel sheets were widely used in the industry due to the advantages in offering high strength with light weight. However, due to the high tensile strength the manufacturing process need to be improved to prevent defects that occurred in the production. Currently, stretch flanging method was used for the manufacturing of steel sheets, however some defects were still observed especially when a long flange length involved. Thus, this research were focusing on minimizing fracture by enhancing the flange length of the stretch flanged steel sheet by using three different approaches namely the side stopper punch shape; application of collar length and pre-heating of the steel sheets before stretch flanging process. The research started with preliminary experiment to test the limit for normal flat-bottom punch with considering a few parameters such as maximum flange length, springback, and thickness distribution. Then, heat was used in the experiment by pre-heating the sheets before being stretch-flanged to improve the formability of the sheets. Side-stopper punch was fabricated and tested with the same setup used in the previous experiment. Another method used with side-stopper punch was the application of collar bending before the stretch flanging take places. From the experiment, it was showed that flat-bottom punch achieved maximum flange length of 12 mm and not achieving the targeted 18 mm. The hot-stretch flanging process was proven to improve the formability as the maximum flange length achieved was 24 mm and the springback was reduced to the maximum of 5° and in aspect of thickness distribution, the thickness at the center of the flanged part were decreased by only 0.2 mm and the thickening recorded were 0.15 mm. Besides, it can be concluded that collar length was a success as the maximum flange length increased to 24 mm while the side stopper punch achieved maximum of 16 mm flange length. For stretch flanging process with collar length, the maximum flanges length of high strength steel sheet increased by 50% compared to stretch flanging process without collar length. The angle of springback was decreased while the thickness at center increased was also show good finished product of high strength steel sheet in stretch flanging process. For comparison, between these three methods, the hot stretch flanging shows the most excellent results due to the flange length, springback and thickness distribution. For cold flanging, the collar bending was the best methods compared to the conventional methods.